Oxidative altered coal from the Upper Silesian Coal Basin - Klika,Z. (Journal of the Czech Geological Society, 1999)
Bituminous coal seams in proximity to or in direct contact with red beds bodies of the Upper Silesian Coal Basin (USCB) are found to be altered by oxidation and elevated temperature. This paper is concerned with oxidative altered coal from Doubrava Mine and Landek Hill where coal seams crop out at the surface. Characteristics of coal in seams exposed to the surface (Landek Hill) are similar to altered coal from Doubrava Mine. Namely it is: high concentrations of oxygen, retrogradely formed humic acids, low concentration of hydrogen and low caloricity heat. The difference between these coals is in presence of sulphate mineralization and in considerable increase of trace elements (B, As, Sr, Ba) and ammonia in coal occuring near red beds. In light of earlier geological studies, the similar characteristics of coals from Doubrava Mine, Landek Hill and the laboratory results, the postdepositional oxidation under low thermal conditions (up to 150 -C) as a possible process of coal alteration is proposed for coal from Doubrava Mine
Keywords: Coal; red beds; oxidation; coal weathering